Biomimetic Behaviours in Hydrogel Artificial Cells through Embedded Organelles - Allen,ME; Hindley,J; O'Toole,N; Cooke,H; Contini,C; Law,R; Ces,O; Elani,Y (Proceedings of the National Academy of Sciences of USA, 2023)
Artificial cells are biomimetic structures formed from molecular building blocks that replicate biological processes, behaviors, and architectures. Of these building blocks, hydrogels have emerged as ideal, yet underutilized candidates to provide a gel-like chassis in which to incorporate both biological and nonbiological componentry which enables the replication of cellular functionality. Here, we demonstrate a microfluidic strategy to assemble biocompatible cell-sized hydrogel-based artificial cells with a variety of different embedded functional subcompartments, which act as engineered synthetic organelles. The organelles enable the recreation of increasingly biomimetic behaviors, including stimulus-induced motility, content release through activation of membrane-associated proteins, and enzymatic communication with surrounding bioinspired compartments. In this way, we showcase a foundational strategy for the bottom–up construction of hydrogel-based artificial cell microsystems which replicate fundamental cellular behaviors, paving the way for the construction of next-generation biotechnological devices.